Health-related quality of life in long-term survivors with localised prostate cancer by therapy: results from a population-based study - Adam, Salome; Brenner, Hermann; Arndt, Volker (European journal of cancer care, 2019)
Objective: Several therapies for localised prostate cancer (PC) are available; all yield similar survival rates. However, each therapy has significant side effects that can influence patients' health-related quality of life (HRQoL) in the long run. Methods: The study sample included 911 survivors with localised PC, 5-15 years post-diagnosis who were identified from the population-based CAESAR + study in Germany. HRQoL was assessed using the EORTC QLQ-C30 and EORTC QLQ-PR25 questionnaires. The association between type of therapy and HRQoL was assessed with multivariable linear regression and global F-test adjusting for age, time since diagnosis and comorbidities. Results: Overall, survivors treated with radical prostatectomy (RP) or radiotherapy (RT) alone reported the best HRQoL and the lowest symptom burden. Conversely, survivors treated with androgen deprivation therapy (ADT) (& RP/RT) or RP & RT (in combination) reported the worst HRQoL and the highest symptom burden. Significant differences among treatment groups in HRQoL were found for global health status (p = 0.041), social functioning (p = 0.007), urinary symptoms (p = 0.035), bowel symptoms (p = 0.017) and hormonal treatment-related symptoms (p < 0.001) among other symptoms. Conclusions: Long-term localised PC survivors formerly treated with a combination of RP and RT or with ADT report poorer HRQoL and more symptoms than patients treated with either RP or RT alone.
Gesehen am 21.10.2019